Abnormalities in male gametophytes development responsible for low seed set of Peudosasa subsolida - Bonan Jiang; Zhihua Cao; Dejia Yang; Yongmei Wang; Yingchun Ma; Shiqi Zhang; Hui Zhan; Lixia Yu; Shuguang Wang; Juan Li (PLoS ONE, 2025)
Pseudosasa subsolida belongs to the Pseudosasa genus within the Poaceae family. Due to its unique flowering cycle and the physiological traits associated with asexual reproduction, acquiring floral material from P. subsolida is particularly challenging. To investigate the causes of the low seed set rate in P. subsolida, floral organs and the development of male and female gametes were examined using conventional paraffin sectioning. The results revealed that the spikelet of P. subsolida exhibited the characteristics of a pseudospikelet with a latent bud, while the inflorescence displayed traits of an infinite inflorescence. Each spikelet contained approximately 10–16 florets and was accompanied by two bracts at its base. The fundamental structure of the florets comprised one lemma, one palea, three lodicules, three stamens, and one pistil. At the later stages of anther development, some abnormalities were observed, including the failure of pollen grains to form, deformation and shrinkage of the cells in the anther sac and tapetum, loss of the cells in the middle layer, cavitation of the microspores, and no identifiable contents The study concluded that the primary factor contributing to the low seed setting rate of P. subsolida was the aberrant development of male gametophytes. The significance of this study lay in its pioneering exploration of the reproductive structure of P. subsolida, and provide a theoretical reference for the fundamental examination of flower structure.